Evaluating a course : practical strategies for teachers, lecturers and trainers - Forsyth, Ian.; Jolliffe, Alan.; Stevens, David (London : Kogan Page, 1999)
This practical guide demonstrates the place of different types of assessment in education. There are tables, charts, figures and practical tips to help make course evaluation easier. This edition includes information on using the Internet as part of a course.
Includes bibliographical reference and index.
Keywords: Teaching -- Evaluation; Instructional systems -- Evaluation; Lesson planning